Evaluation of the association between fear of COVID-19 and pregnancy distress - Mamuk, Rojjin; Akbulut, Şahide; Erdoğan, Ayfer (Makerere University, Medical School, 2023)
Background: Mental health problems experienced during pregnancy negatively affect both maternal and fetal wellbeing. Objective: This study aimed to investigate the relationship between fear of COVID-19 and pregnancy distress in healthy pregnant women living in Turkey. Methods: A descriptive, relational/cross-sectional study was conducted by interviewing 363 pregnant women in person. Data were collected using a personal information form, the Fear of COVID-19 Scale (FCV-19S), and the Tilburg Pregnancy Distress Scale (TPDS). Results: The mean FCV-19S score was 19.03±5.65 and the mean TPDS score was 19.97±7.97. According to the TPDS cut-off score, 19.0% of the participants were at risk of pregnancy distress. There was a significant positive correlation between FCV-19S and TPDS scores (r = 0.263, p<0.05). According to the regression analysis, age (β=-0.217), years of education (β=-0.272), and number of births (β= 0.502) were associated with fear of COVID-19, and fear of COVID-19 was associated with TPDS scores (β= 0.369) (p<0.05). Conclusion: The pregnant women in this study had moderate fear of COVID-19. Compared to the literature data, the prevalence of pregnancy distress was slightly higher than pre-COVID-19 reports but quite low compared to other studies conducted during the pandemic.
Keywords: COVID-19; Distress; Fear; Pregnancy; Pregnant women